Ultrastructure and molecular phylogeny of four new species of monoxenous trypanosomatids from flies (Diptera: Brachycera) with redefinition of the genus Wallaceina - Yurchenko, Vyacheslav; Votýpka, Jan; Tesarová, Martina; Klepetková, Helena; Kraeva, Natalya; Jirků, Milan; Lukes, Julius (Folia parasitologica, 2014)
Four new species of monoxenous kinetoplastid parasites are described from Brachycera flies, namely Wallaceina raviniae Votýpka et Lukes, 2014 and Crithidia otongatchiensis Votýpka et Lukes, 2014 from Ecuador, Leptomonas moramango Votypka et Lukes, 2014 from Madagascar, and Crithidia pragensis Votýpka, Klepetková et Lukes, 2014 from the Czech Republic. The new species are described here based on sequence analysis of their spliced leader (SL) RNA, glycosomal glyceraldehyde 3-phosphate dehydrogenase (gGAPDH) and small subunit (SSU) rRNA genes, as well as their morphology and ultrastructure. High-pressure freezing and Bernhard's EDTA regressive staining, used for the first time for monoxenous (one host) trypanosomatids, revealed the presence of viral particles with cytosolic localization in one and unique mitochondrial localization in another species. In accordance with previous observations, our results emphasize a discrepancy between morphology and molecular taxonomy of the family Trypanosomatidae. All four newly described species are represented by typical morphotypes (mainly choano- and promastigotes) and are virtually indistinguishable from other monoxenous trypanosomatids by morphology. Nevertheless, they all differ in their phylogenetic affinities. Whereas three of them grouped within the recently defined subfamily Leishmaniinae, which includes numerous representatives of the genera Leishmania Ross, 1903, Crithidia Léger, 1902 and Leptomonas Kent, 1880, the fourth species clusters together with the 'collosoma' clade (named after 'Leptomonas' collosoma Wallace, Clark, Dyer et Collins, 1960). Here we demonstrate that the 'collosoma' group represents the elusive genus Wallaceina Podlipaev, Frolov et Kolesnikov, 1999. We redefine this genus in molecular terms based on similarities of the respective molecular markers and propose to use this taxon name for the group of species of the 'collosoma' clade.
Keywords: interakce hostitele a parazita; Animals; druhová specificita; zvířata; Diptera; Phylogeny; fylogeneze; Host-Parasite Interactions; Species Specificity; Trypanosomatina